Enhancement of Aqueous Solubility of Corn Oil using Hydrotropes - Naresh, C.; Gurumurthy, Sivakumaran; Thenesh Kumar, S. (Asian Journal of Chemistry, 2012)
This paper presents a comprehensive study on the effect of hydrotropes on the solubility, mass transfer coefficients of corn oil in water using various hydrotropes such as sodium benzoate, sodium salicylate and sodium acetate trihydrate under a influence of wide range of concentrations 0-3.3 mol/L and system temperature of 303 K. It was found that the solubility and mass transfer coefficients increases with increase in the hydrotropic concentration. The performance of hydrotropes was measured in terms of setschenow constant, ks. Effective mass transfer coefficient was found and reported for all the hydropes used in this study.